Sosialisasi Panduan Penggunaan Transportasi Publik Massal Jabodetabek di Panti Asuhan Darushsholihat Kota Bogor - Sri Handayani; Sonya Sidjabat; Patrick Ivan; Safira Febriyanti (Institut Transportasi dan Logistik Trisakti, 2021)
The population and the high travel needs for Jabodetabek residents, make mass public transportation become important today. There are only two options available, whether using own vehicles or public transportation. The choice of using public transportation is an important thing for the people to do, considering that quite a lot of public transportation has been provided by the government to connect these cities. Mass public transportation available to serve the people of Jakarta and surrounding cities such as Bogor, Depok, Tangerang and Bekasi are Commuter Line, Light Rail Transit (LRT) and Feeder Bus. The government is committed to developing and supporting an integrated transportation system. As a form of higher education concern for the transportation community, it is to carry out advocacy so that people want to use the mass public transportation provided by the Government. Massive and intense socialization to the public about how to use public transportation properly and comfortably continues so that order, comfort and safety in using mass public transportation can be carried out. The socialization was held at the Darushsholihat Orphanage in Bogor City by offline and online. To measure the success of the socialization, the respondents are given a pre-test before the socialization was carried out and a post-test after the socialization was carried out. The results of the socialization indicated an increase in knowledge, understanding and preference for the use of Jabodetabek mass public transportation.